Beneficiation of Low-Grade Dilband Iron Ore by Reduction Roasting - Ali Dad Chandio; Iftikhar Ahmed Channa; Asif Ahmed Shaikh; Shabbir Madad; Syed Bilal Hasan Rizvi; Aqeel Ahmed Shah; Jaweria Ashfaq; Muhammad Ali Shar; Abdulaziz Alhazaa (Metals, 2023)
This research is aimed at the up-gradation of indigenous Pakistani iron ore, i.e., Dilband iron ore (hematite), by utilizing common metallurgical processes. First, the magnetic properties of the ore were determined. Initially, the iron ore samples contained 34 wt. % Fe in addition to other gangue materials. Therefore, the ore was subjected to a high-temperature reduction roasting process between 800 °C and 1000 °C. Additionally, the magnetic separation process was also employed. The influence of different roasting parameters, such as the reduction time, coal-to-ore ratio, and temperature, was examined. This was followed by characterization techniques using XRD (X-ray diffraction analysis), the Rietveld method, wet chemistry analysis, and a VSM (Vibrating Sample Magnetometer). The results suggest an excellent reduction at 900 °C for a coal/ore ratio of 20 wt. %, which was achieved within 2 h of the process. The Fe concentration increased tremendously from 34 to 56 wt. %, and in conjunction, magnetic properties were also induced (1.5 emu). The recovery was found to be substantial for the ore when the Fe content was 75 wt. %. Additionally, the economic feasibility of the processed ore was also studied, followed by an extensive analysis of the roasting and magnetic separation processes.